A colored chemically strengthened glass and its preparation method and application
Chemically strengthened by specific composition base glass and combined with additives, the safety hazards caused by small fragments after falling of chemically strengthened glass are solved, and high strength, high safety and aesthetic performance are achieved.
Patent Information
- Application Number
- CN202310787650.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-06-29
AI Technical Summary
The existing chemically reinforced glass produces small fragments after falling, which leads to safety hazards and is difficult to take into account high strength, high safety and aesthetic performance.
Chemical strengthening is performed using a substrate glass composed of a specific mole percentage, including SiO2, Al2O3, B2O3, Y2O3, La2O3, MgO, Na2O, Li2O and Er2O3. Through single or multi-step chemical strengthening treatment, combined with an appropriate amount of additives to obtain the appropriate color.
Improves the impact and crack propagation resistance of chemically reinforced glass, ensuring high safety and aesthetic performance, while controlling fragment size to reduce splash risk.
Smart Images

Figure CN117865464B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of tempered glass, and in particular to a colored chemically tempered glass and a preparation method and application thereof. Background Art
[0002] In recent years, chemically strengthened glass has been widely used to protect the display devices of electronic products, portable information terminals (PDAs), tablet terminals and other mobile devices; especially for display protection covers and back covers of mobile phones. As we all know, chemically strengthened glass has deep tensile stress and surface compressive stress, which can have good drop resistance, monomer performance, impact resistance, etc. However, for electronic products, after a fall, the glass fragments are small and will cause splashing everywhere, thus causing safety hazards. In addition, if the display screen of an electronic product is broken into small fragments, it is difficult to continue to use it.
[0003] Depending on the final application of the glass, it is desirable for the chemically strengthened glass to exhibit high strength, high safety and also exhibit some corresponding aesthetic properties, such as favorable color.
[0004] Therefore, in the prior art, there is chemically strengthened glass which has high strength so that it has high drop resistance while taking into account high safety and also has a desired color. Summary of the invention
[0005] In view of the above problems, the technical problem to be solved by the present invention is to provide a colored chemically strengthened glass which has high strength so as to have high drop resistance while taking into account high safety and also has a desired color.
[0006] Specifically, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a colored chemically strengthened glass, wherein the colored chemically strengthened glass is obtained by chemically strengthening a substrate glass, and the substrate glass comprises the following components in terms of molar percentage:
[0008] SiO2 58.00~75.00mol%;
[0009] Al2O38.00~16.00mol%;
[0010] B2O3 0.00~5.00mol%;
[0011] Y2O31.00~8.00mol%;
[0012] La2O3 0.10-5.00mol%;
[0013] MgO 1.00~8.00mol%;
[0014] Na2O 3.00~8.00mol%;
[0015] Li2O 7.00~15.00mol%;
[0016] Er2O30.10~2.00mol%.
[0017] In some embodiments of the present invention, the Al2O3 is 9.00-13.00 mol% in mole percentage;
[0018] And / or, in terms of molar percentage, the B2O3 is 0.50 to 1.00 mol%;
[0019] And / or, in terms of molar percentage, the Y2O3 is 1.50 to 3.00 mol%;
[0020] And / or, in terms of molar percentage, the La2O3 is 0.50 to 1.50 mol%;
[0021] And / or, in terms of molar percentage, the MgO is 2.00 to 6.00 mol%;
[0022] And / or, in terms of molar percentage, the Na2O is 4.00-7.00 mol%;
[0023] And / or, in terms of molar percentage, the Li2O is 8.00 to 12.00 mol%;
[0024] And / or, in terms of molar percentage, the Er2O3 is 0.50-1.50 mol%.
[0025] And / or, in terms of molar percentage, the sum of SiO2+Al2O3 in the substrate glass is greater than or equal to 72%, preferably 72-76%.
[0026] In some embodiments of the present invention, the components of Er2O3, Y2O3, MgO and Al2O3 in the substrate glass satisfy the following relationship in terms of molar percentage:
[0027] 0<Er2O3 / (2.450×Y2O3+1.620×MgO+1.078×Al2O3)≤0.076.
[0028] In some embodiments of the present invention, the Young's modulus of the substrate glass is ≥80 GPa, preferably 80 GPa≤Young's modulus≤100 GPa.
[0029] In some embodiments of the present invention, the CIELAB color chromaticity index of the substrate glass at a thickness of 0.7 mm under CIE light source D65 is: L* value is 91.00 to 97.00, a* value is 1.00 to 10.00, and b* value is -4.00 to -0.10.
[0030] In some embodiments of the present invention, the bifurcation threshold of the substrate glass is 39000 MPa / mm to 60000 MPa / mm, preferably 39000 MPa / mm to 50000 MPa / mm.
[0031] In some embodiments of the present invention, the chemical strengthening of the substrate glass includes single-step chemical strengthening or multi-step chemical strengthening.
[0032] In some embodiments of the present invention, the single-step chemical strengthening uses a salt bath containing NaNO3, and preferably the content of NaNO3 is 30-100wt%.
[0033] Preferably, the single-step chemical strengthening uses a mixed salt bath containing NaNO3 and KNO3, and preferably the content of KNO3 in the mixed salt bath is 80-100wt%, and the content of NaNO3 is 0-20wt%.
[0034] More preferably, the temperature of the single-step chemical strengthening is 380-480° C., and more preferably, the ion exchange time of the single-step chemical strengthening is 5-10 h.
[0035] In some embodiments of the present invention, the multi-step chemical strengthening includes two steps of chemical strengthening, wherein the first step of chemical strengthening uses a salt bath containing NaNO3, preferably the content of NaNO3 is 30-100wt%; the second step of chemical strengthening uses a salt bath containing KNO3, preferably the content of KNO3 is 60-100wt%.
[0036] Preferably, the first step of chemical strengthening uses a mixed salt bath containing NaNO3 and KNO3, wherein the content of NaNO3 is 30-100wt%, and the content of KNO3 is 0-70wt%; the second step of chemical strengthening uses a mixed salt bath containing NaNO3 and KNO3, wherein the content of KNO3 is 80-100wt%, and the content of NaNO3 is 0-20wt%.
[0037] More preferably, the temperature of the first step of chemical strengthening is 380-480° C., and the preferred ion exchange time is 3-10 h.
[0038] More preferably, the temperature of the second step chemical strengthening is 380-480° C., and the preferred ion exchange time is 1-5 h.
[0039] In some embodiments of the present invention, the CS_50 of the colored chemically strengthened glass is 40 MPa to 120 MPa, preferably, the CS_50 is 60 MPa to 110 MPa; more preferably, the CS_50 is 80 MPa to 110 MPa.
[0040] In some embodiments of the present invention, DOL_0 of the colored chemically strengthened glass is 0.14t≤DOL_0≤0.25t, where t is the thickness of the colored chemically strengthened glass.
[0041] In some embodiments of the present invention, the CT_LD of the colored chemically strengthened glass is 40000 MPa / mm to 60000 MPa / mm. Preferably, the CT_LD value is 40000 MPa / mm to 55000 MPa / mm.
[0042] In some embodiments of the present invention, the CT_LD value of the colored chemically strengthened glass is ≤1.2 times the bifurcation threshold of the base glass.
[0043] In some embodiments of the present invention, the colored chemically strengthened glass has an average sandpaper drop resistance height greater than 1.60 m, preferably 1.65 to 2.00 m, obtained by performing a sandpaper drop resistance test on the colored chemically strengthened glass at a thickness of 0.7 mm using 120-grit sandpaper.
[0044] In some embodiments of the present invention, the average value of the percentage of broken pieces of the colored chemically strengthened glass is greater than 80%;
[0045] The average value of the percentage of broken pieces after falling refers to the value obtained by dividing the sum of the percentage of broken pieces after falling of at least 5 glass samples by the number of glass samples;
[0046] The proportion of broken fragments when the glass sample falls refers to the proportion of the weight of the sieve residue to the weight of the glass sample after each glass sample is subjected to a sandpaper drop resistance test with 120 mesh sandpaper at a thickness of 0.7 mm; the weight of the glass sample is the weight of the glass sample weighed before the entire machine falls; the weight of the sieve residue is the weight of the glass sample after it is sieved through a 4-mesh sieve with an aperture of 5.16 mm after it falls and breaks, and the weight of the sieve residue is taken out and weighed.
[0047] In some embodiments of the present invention, the maximum vertical projection size of the average fragments of the colored chemically strengthened glass is 4 mm to 35 mm;
[0048] The average maximum vertical projection size of the fragments refers to the value obtained by dividing the sum of the average values of the maximum vertical projection sizes of the fragments of at least 5 glass samples by the number of glass samples;
[0049] The average value of the maximum vertical projection size of the fragments of the glass sample refers to the average value of the maximum vertical projection size of all glass fragments with a maximum vertical projection size greater than 1 mm after each glass sample is subjected to a sandpaper drop resistance test with 120-mesh sandpaper at a thickness of 0.7 mm.
[0050] In a second aspect, the present invention provides a method for preparing the above-mentioned colored chemically strengthened glass, comprising the following steps:
[0051] (1) selecting raw material components according to the composition of the substrate glass, mixing them, melting and forming them, and then cooling and annealing them to obtain the substrate glass;
[0052] (2) Chemically strengthening the base glass to obtain colored chemically strengthened glass.
[0053] In some embodiments of the present invention, the chemical strengthening includes single-step chemical strengthening or multi-step chemical strengthening.
[0054] In some embodiments of the present invention, the single-step chemical strengthening uses a salt bath containing NaNO3, and preferably the content of NaNO3 is 30-100wt%.
[0055] Preferably, the single-step chemical strengthening uses a mixed salt bath containing NaNO3 and KNO3, and preferably the content of KNO3 in the mixed salt bath is 80-100wt%, and the content of NaNO3 is 0-20wt%.
[0056] More preferably, the temperature of the single-step chemical strengthening is 380-480° C., and the ion exchange time of the single-step chemical strengthening is preferably 5-10 h.
[0057] In some embodiments of the present invention, the multi-step chemical strengthening includes two steps of chemical strengthening, wherein the first step of chemical strengthening uses a salt bath containing NaNO3, preferably the content of NaNO3 is 30-100wt%; the second step of chemical strengthening uses a salt bath containing KNO3, preferably the content of KNO3 is 60-100wt%.
[0058] Preferably, the first step of chemical strengthening uses a mixed salt bath containing NaNO3 and KNO3, wherein the content of NaNO3 is 30-100wt%, and the content of KNO3 is 0-70wt%; the second step of chemical strengthening uses a mixed salt bath containing NaNO3 and KNO3, wherein the content of KNO3 is 80-100wt%, and the content of NaNO3 is 0-20wt%.
[0059] More preferably, the temperature of the first step of chemical strengthening is 380-480° C., and the preferred ion exchange time is 3-10 h.
[0060] More preferably, the temperature of the second step chemical strengthening is 380-480° C., and the preferred ion exchange time is 1-5 h.
[0061] In a third aspect, the present invention provides a use of the above-mentioned colored chemically strengthened glass or the colored chemically strengthened glass prepared by the above-mentioned preparation method in a mobile phone display screen, a tablet computer display screen, a handheld game console, an electronic terminal, a portable digital device, a vehicle central control screen, an electronic whiteboard glass, a smart home touch screen, a vehicle windshield, an aircraft windshield or an aircraft windshield.
[0062] Compared with the prior art, the present invention has the following beneficial effects:
[0063] 1. The present invention uses erbium oxide as a colorant for the base glass, and after chemical strengthening, the CS_50 and D0L_0 of the chemically strengthened glass are improved, thereby improving the impact resistance and crack growth resistance of the chemically strengthened glass, that is, the drop resistance performance.
[0064] 2. The present invention reasonably controls the content of erbium oxide, so that the colored chemically strengthened glass has both high strength and high safety.
[0065] 3. The invention adds additives and combines them with erbium oxide to make the prepared colored chemically strengthened glass have desirable and pleasing colors. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] Figure 1 Schematic diagram of the stress release device for the immediate fracture test; the markings in the figure are as follows: 1-height adjustment rail, 2-start adjustment rail, 3-pressing head, 4-chemically strengthened glass sample.
[0067] Figure 2 This is the crack damage state diagram of the immediate fracture test.
[0068] Figure 3 The figures are the drop and breakage results of the colored chemically strengthened glass prepared in Examples 3-4 and the drop and breakage results of the chemically strengthened glass prepared in Comparative Examples 1 and 2. DETAILED DESCRIPTION
[0069] The present invention will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the present invention belong to the scope of protection of the present invention.
[0070] The relevant special terms involved in the present invention are explained as follows.
[0071] In the present invention, the base glass refers to glass obtained by mixing raw materials, melting and forming, and then cooling and annealing.
[0072] In the present invention, chemically strengthened glass refers to a solid composite material obtained by chemically strengthening the base glass.
[0073] It should be understood that during high-temperature chemical strengthening treatment, alkali metal ions with large ionic radius (such as potassium ions and sodium ions) in the salt bath / molten salt will replace alkali metal ions with small ionic radius (such as sodium ions and lithium ions) in the substrate glass, thereby generating an exchange ion volume difference and generating compressive stress on the glass surface.
[0074] In the present invention, surface CS refers to surface compressive stress or surface compression stress. After the substrate glass is chemically strengthened, the alkali metal ions with a smaller radius on the surface are replaced by alkali metal ions with a larger radius. Due to the crowding effect of the alkali metal ions with a larger radius, compressive stress is generated on the glass surface, which is called surface compressive stress.
[0075] In the present invention, DOL_0 refers to the depth of the compressive stress layer, also known as the depth of the compressive stress layer, which refers to the distance from any surface of the glass to a position close to the surface where the compressive stress is zero.
[0076] In the present invention, CS_50 refers to the compressive stress value at a depth of 50 μm from the glass surface.
[0077] In the present invention, |CT_AV| refers to the absolute value of the average tensile stress in the tensile stress layer of the glass, specifically refers to the absolute value of the average value of all tensile stresses in the tensile stress layer.
[0078] In the present invention, CT_LD refers to the ratio of the definite integral of the tensile stress curve of chemically strengthened glass to the thickness of the chemically strengthened glass, which is recorded as the tensile stress linear density. The substrate glass is placed in a salt bath for ion exchange to form a strengthening layer (i.e., a compressive stress layer). During the ion exchange process, a tensile stress layer is formed inside the glass, and the tensile stress layer has an upper boundary that is spaced a certain distance from the upper surface of the chemically strengthened glass and a lower boundary that is spaced a certain distance from the lower surface of the chemically strengthened glass. A curve drawn with the tensile stress magnitude at a point on a line segment in the tensile stress layer that is perpendicular to the upper boundary and the lower boundary and whose upper and lower endpoints fall on the upper boundary and the lower boundary respectively as the Y axis and the distance from the corresponding point to the upper boundary as the X axis is recorded as the tensile stress curve, and the ratio of the definite integral of the tensile stress curve to the thickness of the chemically strengthened glass is recorded as the tensile stress linear density, which is the ratio of the sum of the tensile stresses of the chemically strengthened glass measured by the SLP-2000 stress meter to the glass thickness.
[0079] In the present invention, CT_LD maxRefers to the maximum value of tensile stress line density. The maximum tensile stress line density (CT_LD) value that can be obtained by ion exchange chemical strengthening of substrate glass under specific salt bath conditions is the maximum tensile stress line density CT_LD that can be obtained by substrate glass under the salt bath conditions. max This data can characterize the strengthenability / ion exchangeability of the substrate glass.
[0080] In the present invention, the bifurcation threshold refers to the minimum tensile stress linear density value of the chemically strengthened glass prepared from a certain formula base glass when the glass crack bifurcates in an immediate fracture test, that is, the bifurcation threshold of the chemically strengthened glass prepared from the formula base glass.
[0081] After repeated experiments and research, the inventors found that by adding erbium oxide to the specific composition of the substrate glass, the chemical strengthening of the substrate glass can be beneficially affected, and the CS_50 and DOL_0 of the chemically strengthened glass can be improved; and the increase in the CS_50 value can enhance the drop resistance of the chemically strengthened glass; the increase in DOL_0 will also make the chemically strengthened glass more resistant to crack propagation, that is, the drop resistance of the chemically strengthened glass can be enhanced. However, on the other hand, adding too much Er2O3 to the substrate glass will reduce the bifurcation threshold of the substrate glass, so that the resulting chemically strengthened glass will have smaller fragments when it falls, which reduces the safety performance.
[0082] Based on the above viewpoints, in order to obtain a chemically strengthened glass having high strength, i.e., high drop resistance, and high safety; the present invention provides a colored chemically strengthened glass, wherein the colored chemically strengthened glass is obtained by chemically strengthening a base glass, and the base glass comprises the following components in terms of molar percentage:
[0083] SiO2 58.00~75.00mol%;
[0084] Al2O38.00~16.00mol%;
[0085] B2O3 0.00~5.00mol%;
[0086] Y2O31.00~8.00mol%;
[0087] La2O3 0.10-5.00mol%;
[0088] MgO 1.00~8.00mol%;
[0089] Na2O 3.00~8.00mol%;
[0090] Li2O 7.00~15.00mol%;
[0091] Er2O30.10~2.00mol%.
[0092] In addition, the present invention has found that erbium oxide only exhibits a single pink color, which makes the color of the chemically strengthened glass obtained single and cannot obtain a pleasing color; by adding an appropriate amount of additives and combining colors with erbium oxide, a colored chemically strengthened glass with a desired pleasing color can be prepared.
[0093] In order to make the obtained colored chemically strengthened glass have a desired pleasing color, the present invention further provides a colored chemically strengthened glass, wherein the colored chemically strengthened glass is obtained by chemically strengthening a substrate glass, and the substrate glass comprises the following components in molar percentage:
[0094] SiO2 58.00~72.00mol%;
[0095] Al2O38.00~15.00mol%;
[0096] B2O3 0.00~5.00mol%;
[0097] Y2O31.00~8.00mol%;
[0098] La2O3 0.10-5.00mol%;
[0099] MgO 3.00~8.00mol%;
[0100] Na2O 3.00~8.00mol%;
[0101] Li2O 7.00~15.00mol%;
[0102] Er2O3 0.50~2.00mol%;
[0103] and 0.005-2.0 mol% of an additive; the additive is selected from one or more of CoO, Ho2O3, MnO, Nd2O3, and Cr2O3.
[0104] In some embodiments of the present invention, the substrate glass of the present invention comprises 0.10-1.90 mol% Er2O3 by mole percentage. In some embodiments of the present invention, the substrate glass of the present invention comprises 0.10-1.80 mol%, 0.10-1.70 mol%, 0.10-1.60 mol%, 0.10-1.50 mol%, 0.10-1.40 mol%, 0.10-1.30 mol%, 0.10-1.20 mol%, 0.10-1.10 mol%, 0.10-1.00 mol%, 0.10-0.90 mol%, 0.10-0.80 mol%, 0.10-0.70 mol%, 0.10-0.60 mol%, 0. .10~0.50mol%, 0.20~2.00mol%, 0.30~2.00mol%, 0.40~2.00mol%, 0.50~2.00mol%, 0.60~2.00mol%, 0.70~2.00mol%, 0.80~2.00mol%, 0.90~2.00mol%, 1.00~2.00mol%, 1.10~2.00mol%, 1.20~2.00mol%, 1.30~2.00mol%, 1.40~2.00mol%, 1.50~2.00mol% Er2O3. In some embodiments of the present invention, the substrate glass of the present invention includes 0.10 mol%, 0.20 mol%, 0.30 mol%, 0.40 mol%, 0.50 mol%, 0.60 mol%, 0.70 mol%, 0.80 mol%, 0.90 mol%, 1.00 mol%, 1.10 mol%, 1.20 mol%, 1.30 mol%, 1.40 mol%, 1.50 mol%, 1.60 mol%, 1.70 mol%, 1.80 mol%, 1.90 mol% or 2.00 mol% of Er2O3, or Er2O3 within a numerical range consisting of any two of the above specific numerical values as endpoints. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges.
[0105] SiO2 is a glass network forming oxide and an indispensable component of the glass network structure. In some embodiments of the present invention, the substrate glass of the present invention comprises, by mole percentage, 58.00-74.00 mol%, 58.00-73.00 mol%, 58.00-72.00 mol%, 58.00-71.00 mol%, 58.00-70.00 mol%, 58.00-69.00 mol%, 58.00-68.00 mol%, 58.00-67.00 mol%, 58.00-66.00 mol%, 58.00-65.00 mol%, 58.00-64.00 mol%, 58.00-63.0 % SiO2. In some embodiments of the present invention, the substrate glass of the present invention includes 58.00mol%, 59.00mol%, 60.00mol%, 61.00mol%, 62.00mol%, 63.00mol%, 64.00mol%, 65.00mol%, 66.00mol%, 67.00mol%, 68.00mol%, 69.00mol%, 70.00mol%, 71.00mol%, 72.00mol%, 73.00mol% or 74.00mol% SiO2, or SiO2 within a numerical range consisting of any two of the above specific values as endpoints, in molar percentage. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges.
[0106] Al2O3 is also a network component. Al2O3 forms aluminum-oxygen tetrahedrons in the glass and connects the non-bridging oxygen in the silicon-oxygen network structure, thereby improving the strength of the network structure, further enhancing the strength and stability of the glass, and greatly improving the chemical stability of the glass. In some embodiments of the present invention, the substrate glass of the present invention includes, in molar percentage, 8.00-15.50mol%, 8.00-15.00mol%, 8.00-14.50mol%, 8.00-14.00mol%, 8.00-13.50mol%, 8.00-13.00mol%, 8.00-12.50mol%, 8.00-12.00mol%, 8.00-11.50mol%, 8.00-11.00mol%, 8.00-10.50mol%, 8.00-1 0.00mol%, 8.50-16.00mol%, 9.00-16.00mol%, 9.50-16.00mol%, 10.00-16.00mol%, 10.50-16.00mol%, 11.00-16.00mol%, 11.50-16.00mol%, 12.00-16.00mol%, 12.50-16.00mol%, 13.00-16.00mol%, 13.50-16.00mol% or 14.00-16.00mol% Al2O3. In some embodiments of the present invention, the substrate glass of the present invention includes 8.00 mol%, 8.50 mol%, 9.00 mol%, 9.50 mol%, 10.00 mol%, 10.50 mol%, 11.00 mol%, 11.50 mol%, 12.00 mol%, 12.50 mol%, 13.00 mol%, 13.50 mol%, 14.00 mol%, 14.50 mol%, 15.00 mol%, 15.50 mol% or 16.00 mol% of Al2O3, or Al2O3 within a numerical range consisting of any two of the above specific numerical values as endpoints. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges.
[0107] B2O3 is a network former component of glass; B2O3 can improve the melting process of glass batch materials and can significantly reduce the high-temperature viscosity of molten glass. In some embodiments of the present invention, the substrate glass of the present invention includes, by mole percentage, 0.00-4.50 mol%, 0.00-4.00 mol%, 0.10-3.50 mol%, 0.10-3.00 mol%, 0.10-2.50 mol%, 0.20-2.00 mol%, 0.20-1.50 mol%, 0.20-1.00 mol%, 0.50-5.00 mol%, 1.00-5.00 mol%, 1.50-5.00 mol%, 2.00-5.00 mol%, 2.50-5.00 mol%, 3.00-5.00 mol%, 3.50-5.00 mol% or 4.00-5.00 mol% B2O3. In some embodiments of the present invention, the substrate glass of the present invention includes 0.1 mol%, 0.2 mol%, 0.50 mol%, 1.00 mol%, 1.50 mol%, 2.00 mol%, 2.50 mol%, 3.00 mol%, 3.50 mol%, 4.00 mol%, 4.50 mol% or 5.00 mol% B2O3 in molar percentage, or B2O3 in a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges.
[0108] La2O3 is a network modification component of glass; La2O3 can reduce the high-temperature viscosity of glass, which is beneficial to glass melting and the elimination of internal defects; it can significantly improve the Young's modulus and micro-Vickers hardness of glass. In some embodiments of the present invention, the substrate glass of the present invention includes, by mole percentage, 0.10-4.50 mol%, 0.10-4.00 mol%, 0.10-3.50 mol%, 0.20-3.00 mol%, 0.20-2.50 mol%, 0.30-2.00 mol%, 0.40-1.50 mol%, 0.40-1.00 mol%, 0.50-5.00 mol%, 1.00-5.00 mol%, 1.50-5.00 mol%, 2.00-5.00 mol%, 2.50-5.00 mol%, 3.00-5.00 mol%, 3.50-5.00 mol% or 4.00-5.00 mol% La2O3. In some embodiments of the present invention, the substrate glass of the present invention includes 0.10 mol%, 0.30 mol%, 0.50 mol%, 1.00 mol%, 1.50 mol%, 2.00 mol%, 2.50 mol%, 3.00 mol%, 3.50 mol%, 4.00 mol%, 4.50 mol% or 5.00 mol% La2O3, or La2O3 within a numerical range consisting of any two of the above specific numerical values as endpoints, in molar percentage. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges.
[0109] Y2O3 has the function of making the glass structure compact, and can increase the packing density inside the glass, which is manifested as increasing the glass density, thereby increasing the intrinsic strength of the glass. In some embodiments of the present invention, the substrate glass of the present invention includes, by mole percentage, 1.00-7.50 mol%, 1.00-7.00 mol%, 1.00-6.50 mol%, 1.00-6.00 mol%, 1.00-5.50 mol%, 1.00-5.00 mol%, 1.00-4.50 mol%, 1.00-4.00 mol%, 1.00-3.50 mol%, 1.00-3.00 mol%, 1.50-8.00 mol%, 2.00-8.00 mol%, 2.50-8.00 mol%, 3.00-8.00 mol%, 3.50-8.00 mol%, 4.00-8.00 mol%, 4.50-8.00 mol%, 5.00-8.00 mol%, 5.50-8.00 mol% or 6.00-8.00 mol% Y2O3. In some embodiments of the present invention, the substrate glass of the present invention includes 1.00 mol%, 1.50 mol%, 2.00 mol%, 2.50 mol%, 3.00 mol%, 3.50 mol%, 4.00 mol%, 4.50 mol%, 5.00 mol%, 5.50 mol%, 6.00 mol%, 6.50 mol%, 7.00 mol%, 7.50 mol% or 8.00 mol% of Y2O3, or Y2O3 within a numerical range consisting of any two of the above specific numerical values as endpoints. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges.
[0110] MgO, as a glass network outer body, can adjust the viscosity-temperature performance of the glass by breaking the network and loosening the network structure of the glass, thereby improving the melting performance of the glass. In some embodiments of the present invention, the substrate glass of the present invention includes 1-8.00mol%, 1.50-8.00mol%, 1.00-7.50mol%, 2.00-7.00mol% MgO in mole percentage. In some embodiments of the present invention, the substrate glass of the present invention includes 1.00mol%, 1.50mol%, 2.00mol%, 2.50mol%, 3.00mol%, 3.50mol%, 4.00mol%, 4.50mol%, 5.00mol%, 5.30mol%, 5.50mol%, 6.00mol%, 6.50mol%, 7.00mol%, 7.50mol% or 8.00mol% in mole percentage; or MgO in the numerical range consisting of any two of the above specific values as endpoints. It should be understood that in specific embodiments, any of the above ranges may be combined with any other ranges.
[0111] As the outer body of the glass network, Na2O can loosen the network structure of the glass by breaking the network to form a large amount of non-bridging oxygen, thereby greatly reducing the liquidus temperature and melting temperature of the glass melt and reducing the difficulty of melting the glass. At the same time, the moderate looseness of the glass network structure can further increase the diffusion coefficient of alkali metal ions in the glass and increase the ion exchange rate during chemical strengthening of the glass. In some embodiments of the present invention, in terms of molar percentage, the substrate glass of the present invention includes 3.00-7.50mol%, 3.00-7.00mol%, 3.00-6.50mol%, 3.00-6.00mol%, 3.00-5.50mol%, 3.00-5.00mol%, 3.50-8.00mol%, 4.00-8.00mol%, 4.50-8.00mol%, 5.00-8.00mol%, 5.50-8.00mol% or 6.00-8.00mol% of Na2O. In some embodiments of the present invention, the substrate glass of the present invention includes 3.00 mol%, 3.50 mol%, 4.00 mol%, 4.50 mol%, 5.00 mol%, 5.50 mol%, 6.00 mol%, 6.50 mol%, 7.00 mol%, 7.50 mol% or 8.00 mol% of Na2O, or Na2O within a numerical range consisting of any two of the above specific values as endpoints, in molar percentage. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges.
[0112] Li2O is a key component of sodium-lithium ion exchange in chemical strengthening. Its content directly affects the exchange amount, and thus affects the magnitude of deep stress. However, too much Li2O also destroys the glass network structure, reduces its intrinsic strength, and makes it easier to relax its structure. In some embodiments of the present invention, the substrate glass of the present invention includes, by mole percentage, 7.00-14.00 mol%, 7.00-13.50 mol%, 7.00-13.00 mol%, 7.00-12.50 mol%, or 7.00-12.00 mol%, 7.50-15.00 mol%, 8.00-15.00 mol%, 8.50-15.00 mol%, 9.00-15.00 mol%, 9.50-15.00 mol%, 10.00-15.00 mol%, 10.50-15.00 mol%, 11.00-15.00 mol%, 11.50-15.00 mol%, or 12.00-15.00 mol% Li2O. In some embodiments of the present invention, the substrate glass of the present invention includes 7.00 mol%, 7.50 mol%, 8.00 mol%, 8.50 mol%, 9.00 mol%, 9.50 mol%, 10.00 mol%, 10.50 mol%, 11.00 mol%, 11.50 mol%, 12.00 mol%, 12.50 mol%, 13.00 mol%, 13.50 mol%, 14.00 mol%, 14.50 mol% or 15.00 mol% of Li2O, or Li2O in a numerical range consisting of any two of the above specific values as endpoints, in a specific embodiment. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0113] Sr in SrO 2+It has a larger ionic radius and has the effect of reducing the melting temperature of the glass when the content is low. In some embodiments of the present invention, the substrate glass of the present invention includes 0.00-2.50mol%, 0.00-2.00mol%, 0.20-1.50mol% or 0.20-1.00mol%, 0.50-3.00mol%, 1.00-3.00mol%, 1.50-3.00mol% or 2.00-3.00mol% SrO in mole percentage. In some embodiments of the present invention, the substrate glass of the present invention includes 0.20mol%, 0.50mol%, 1.00mol%, 1.50mol%, 2.00mol%, 2.50mol% or 3.00mol% SrO in mole percentage; or SrO in a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0114] In some embodiments of the present invention, the substrate glass of the present invention further includes 0.005-2.0 mol%, 0.005-1.5 mol%, 0.005-1.0 mol%, 0.005-0.5 mol%, 0.01-1.0 mol%, 0.03-1.0 mol%, 0.05-1.0 mol%, 0.03-0.5 mol%, 0.01-0.5 mol% or 0.01-0.1 mol% of additives; the additives are selected from one or more of CoO, Ho2O3, MnO, Nd2O3, Cr2O3. In some embodiments of the present invention, the substrate glass of the present invention includes 0.005 mol%, 0.10 mol%, 0.20 mol%, 0.30 mol%, 0.50 mol%, 1.00 mol%, 1.50 mol% or 2.00 mol% of additives in molar percentage; the additives are selected from one or more of CoO, Ho2O3, MnO, Nd2O3, Cr2O3; or additives within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges.
[0115] In some embodiments of the present invention, the substrate glass of the present invention may optionally include one or more clarifiers, and the content of the clarifier is not particularly limited, and the content is known in the art. In some embodiments of the present invention, the clarifier may include, for example, NaCl, SnO, SnO2 and / or As2O3.
[0116] SiO2 and Al2O3 are the main components of glass, which play an important role in the chemical stability, thermal stability, mechanical strength, etc. of glass. In some embodiments of the present invention, in terms of molar percentage, the sum of SiO2+Al2O3 in the substrate glass of the present invention is greater than or equal to 72 mol%, preferably 72-76 mol%. In some embodiments of the present invention, in terms of molar percentage, SiO2+Al2O3 in the substrate glass of the present invention is 72.00 mol%, 73.00 mol%, 74.00 mol%, 75.00 mol% or 76.00 mol%; or within the numerical range consisting of any two of the above specific values as endpoints. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges.
[0117] In some embodiments of the present invention, in terms of molar percentage, the components of Er2O3, Y2O3, MgO and Al2O3 in the substrate glass of the present invention satisfy the following relationship: 0<Er2O3 / (2.450×Y2O3+1.620×MgO+1.078×Al2O3)≤0.076. In some embodiments of the present invention, in terms of molar percentage, the value of Er2O3 / (2.450×Y2O3+1.620×MgO+1.078×Al2O3) in the substrate glass of the present invention is 0.004, 0.019, 0.023, 0.031, 0.039, 0.057, 0.061, 0.070, 0.075 or 0.076, or is within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges.
[0118] In some embodiments of the present invention, the thickness of the substrate glass of the present invention is not particularly limited, for example, it can be 0.4 to 2.0 mm; preferably 0.4 to 1.0 mm. In some embodiments of the present invention, the thickness of the substrate glass of the present invention can also be 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 2.0 mm, or a range formed by any two of the above values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0119] In some embodiments of the present invention, the Young's modulus of the substrate glass of the present invention is ≥80GPa, preferably 80GPa≤Young's modulus≤100GPa. In some embodiments, the Young's modulus of the substrate glass of the present invention may be 82-100GPa, 84-100GPa, 86-100GPa, 88-100GPa, 90-100GPa, 80-98GPa, 80-96GPa, 80-94GPa, 80-92GPa or 80-90GPa. In some embodiments, the Young's modulus of the substrate glass of the present invention may be 80GPa, 82GPa, 84GPa, 86GPa, 88GPa, 90GPa, 92GPa, 94GPa, 96GPa, 98GPa or 100GPa; or within the numerical range consisting of any two of the above specific values as endpoints. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges.
[0120] In the present invention, the color of the glass is expressed by the CIE LAB color space. In some embodiments of the present invention, the CIELAB color chromaticity index of the substrate glass of the present invention at a thickness of 0.7 mm under the condition of CIE light source D65 is: L* value is 85.00-97.00, a* value is 1.00-10.00, and b* value is -11.00-6.00; preferably, the CIELAB color chromaticity index of the substrate glass of the present invention at a thickness of 0.7 mm under the condition of CIE light source D65 is: L* value is 86.00-96.80, a* value is 1.00-9.90, and b* value is -10.50-5.50; more preferably, the CIELAB color chromaticity index of the substrate glass of the present invention at a thickness of 0.7 mm under the condition of CIE light source D65 is: L* value is 86.00-96.50, a* value is 1.20-9.90, and b* value is -10.50-5.20.
[0121] In some embodiments of the present invention, the CIELAB color chromaticity index of the substrate glass of the present invention at a thickness of 0.7 mm under the condition of CIE light source D65 is: L* value is 91.00-97.00, a* value is 1.00-10.00, and b* value is -4.00--0.10; preferably, the CIELAB color chromaticity index of the substrate glass of the present invention at a thickness of 0.7 mm under the condition of CIE light source D65 is: L* value is 92.00-96.80, a* value is 1.00-10.00, and b* value is -4.00--0.20; more preferably, the CIELAB color chromaticity index of the substrate glass of the present invention at a thickness of 0.7 mm under the condition of CIE light source D65 is: L* value is 92.50-96.50, a* value is 1.10-9.90, and b* value is -3.80--0.30.
[0122] In some embodiments of the present invention, the CIELAB color chromaticity index of the substrate glass of the present invention at a thickness of 0.7 mm under the condition of CIE light source D65 is: L* value is 85.00~92.50, a* value is 1.00~8.00, and b* value is -11.00~6.00; preferably, the CIELAB color chromaticity index of the substrate glass of the present invention at a thickness of 0.7 mm under the condition of CIE light source D65 is: L* value is 87.00~92.50, a* value is 1.50~7.50, and b* value is -10.50~5.50.
[0123] In some embodiments of the present invention, when the additive is selected from one or more of CoO, Ho2O3 or Nd2O3, the CIELAB color chromaticity index of the substrate glass of the present invention at a thickness of 0.7 mm under the condition of CIE light source D65 is: L* value is 85.00~92.50, a* value is 3.00~8.00, and b* value is -11.00~0.00; preferably, the CIELAB color chromaticity index of the substrate glass of the present invention at a thickness of 0.7 mm under the condition of CIE light source D65 is: L* value is 87.00~92.50, a* value is 3.50~7.50, and b* value is -10.50~-0.40.
[0124] In some embodiments of the present invention, the additive is MnO and / or Cr2O3, and the CIELAB color chromaticity index of the substrate glass of the present invention at a thickness of 0.7 mm under the condition of CIE light source D65 is: L* value is 85.00-90.00, a* value is 1.00-8.00, and b* value is 0.00-6.00; preferably, the CIELAB color chromaticity index of the substrate glass of the present invention at a thickness of 0.7 mm under the condition of CIE light source D65 is: L* value is 86.00-89.00, a* value is 1.50-8.00, and b* value is 1.00-5.50.
[0125] The bifurcation threshold in the present invention is a reference index for the glass to obtain a safe stress tolerance. The lower the value, the smaller the fragments of the chemically strengthened glass made from the base glass will be when it falls, which may cause small fragments to splash and injure people, thus reducing safety. For high safety considerations, in some embodiments of the present invention, the bifurcation threshold of the base glass of the present invention is 39000MPa / mm to 60000MPa / mm, preferably 39000MPa / mm to 50000MPa / mm. In some embodiments of the present invention, the bifurcation threshold of the substrate glass of the present invention can be 39000MPa / mm, 39500MPa / mm, 40000MPa / mm, 40500MPa / mm, 41000MPa / mm, 41500MPa / mm, 42000MPa / mm, 45000MPa / mm, 47000MPa / mm, 50000MPa / mm, 55000MPa / mm, 60000MPa / mm, or a range formed by any two of the above values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0126] In the present invention, CT_LD max It is a characterization of the strengthening performance / ion exchange performance of the substrate glass. In some embodiments of the present invention, the CT_LD of the substrate glass of the present invention is max In some embodiments of the present invention, the CT_LD of the substrate glass of the present invention is 48000MPa / mm to 80000MPa / mm, preferably 48000MPa / mm to 70000MPa / mm. maxThe range formed by 48000MPa / mm, 50000MPa / mm, 52000MPa / mm, 55000MPa / mm, 60000MPa / mm, 62500MPa / mm, 65000MPa / mm, 70000MPa / mm, 72000MPa / mm, 75000MPa / mm, 80000MPa / mm or any two of the above numerical values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0127] In the present invention, the colored chemically strengthened glass is obtained by chemically strengthening the above-mentioned base glass, and the chemical strengthening treatment can be performed by a conventionally known method; for example, the chemical strengthening of the base glass includes single-step chemical strengthening or multi-step chemical strengthening.
[0128] In some embodiments of the present invention, the single-step chemical strengthening uses a salt bath containing NaNO3; preferably, the content of NaNO3 is 30-100wt%; preferably, the single-step chemical strengthening uses a mixed salt bath containing NaNO3 and KNO3, preferably, the content of KNO3 in the mixed salt bath is 80-100wt%, and the content of NaNO3 is 0-20wt%.
[0129] In some embodiments of the present invention, the temperature of the single-step chemical strengthening is 380-480° C., and preferably, the ion exchange time of the single-step chemical strengthening is 5-10 h.
[0130] In some embodiments of the present invention, the multi-step chemical strengthening includes two steps of chemical strengthening, wherein the first step of chemical strengthening uses a salt bath containing NaNO3, preferably the content of NaNO3 is 30-100wt%; the second step of chemical strengthening uses a salt bath containing KNO3, preferably the content of KNO3 is 60-100wt%.
[0131] In some embodiments of the present invention, the first step of chemical strengthening uses a mixed salt bath containing NaNO3 and KNO3, wherein the content of NaNO3 is 30-100wt%, and the content of KNO3 is 0-70wt%; the second step of chemical strengthening uses a mixed salt bath containing NaNO3 and KNO3, wherein the content of KNO3 is 80-100wt%, and the content of NaNO3 is 0-20wt%.
[0132] In some embodiments of the present invention, the temperature of the first step of chemical strengthening is 380-480°C, and the preferred ion exchange time is 3-10h; preferably, the temperature of the second step of chemical strengthening is 380-480°C, and the preferred ion exchange time is 1-5h.
[0133] In the present invention, the thickness t of the colored chemically strengthened glass is not particularly limited, for example, it can be 0.4 to 2.0 mm; preferably 0.4 to 1.0 mm. In some embodiments of the present invention, the thickness t of the colored chemically strengthened glass of the present invention can be 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 2.0 mm, or a range formed by any two of the above values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0134] When chemically strengthened glass is subjected to load and impact, the generated surface compressive stress will offset part of the impact; therefore, the formation of the surface compressive stress layer of chemically strengthened glass can improve the strength and impact resistance of chemically strengthened glass, that is, improve its drop resistance. In some embodiments of the present invention, the DOL_0 of the colored chemically strengthened glass of the present invention is 0.14t≤DOL_0≤0.25t, t is the thickness of the colored chemically strengthened glass; the thickness of the colored chemically strengthened glass before and after chemical strengthening is very small and almost negligible, that is, the thickness of the substrate glass is very small compared with the thickness of the chemically strengthened glass obtained by chemically strengthening the substrate glass. In some embodiments of the present invention, the DOL_0 of the colored chemically strengthened glass of the present invention is preferably 0.14t≤DOL_0≤0.24t; it can also be: 0.14t, 0.15t, 0.154t, 0.16t, 0.165t, 0.17t, 0.175t, 0.18t, 0.19t, 0.20t, 0.21t, 0.22t, 0.23t, 0.24t or 0.25t or a range formed by any two of the above values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0135] The surface CS of chemically strengthened glass is related to the strength of the chemically strengthened glass monomer. The higher the surface CS, the higher its monomer strength. The surface CS_50 of chemically strengthened glass can characterize its ability to resist impact and crack propagation, and further characterize its drop resistance. In some embodiments of the present invention, the CS_50 of the colored chemically strengthened glass of the present invention is 40MPa to 120MPa, preferably, CS_50 is 80MPa to 110MPa. In some embodiments of the present invention, the CS_50 of the colored chemically strengthened glass of the present invention is 40MPa, 45MPa, 50MPa, 55MPa, 60MPa, 65MPa, 70MPa, 75MPa, 80MPa, 82MPa, 84MPa, 86MPa, 88MPa, 90MPa, 92MPa, 94MPa, 96MPa, 98MPa, 100MPa, 102MPa, 106MPa, 108MPa, 110MPa, 112MPa, 115MPa or 120MPa; or is within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0136] In some embodiments of the present invention, the |CT_AV| of the colored chemically strengthened glass of the present invention is 60MPa to 100MPa. In some embodiments of the present invention, the |CT_AV| of the colored chemically strengthened glass of the present invention may be 60.00MPa, 61.00MPa, 62.81MPa, 63.00MPa, 64.00MPa, 65.25MPa, 66.17MPa, 67.04MPa, 67.74MPa, 70.00MPa, 80.00MPa, 85.00MPa, 90.00MPa, 95.00MPa or 100.00MPa; or within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges may be combined with any other ranges.
[0137] The value of the tensile stress linear density CT_LD of chemically strengthened glass is positively correlated with its drop resistance. The larger the CT_LD value, the higher its drop resistance. However, as the CT_LD value increases, the difference between it and the glass bifurcation threshold will gradually increase. When the difference between the two exceeds a certain limit, the probability of the glass breaking into large fragments will decrease, and a large number of small fragments will be produced instead, resulting in touch failure and display failure. In addition, too many small fragments are prone to splashing, causing personal injury. If you want the chemically strengthened glass to remain in larger fragments after breaking, and continue to use it without immediate failure, you need to control the CT_LD value not to exceed the bifurcation threshold too much; preferably, the present invention controls the CT_LD value to not exceed 1.2 times the bifurcation threshold of the substrate glass.
[0138] In some embodiments of the present invention, the CT_LD value of the colored chemically strengthened glass of the present invention is 40000MPa / mm to 60000MPa / mm, preferably, the CT_LD value is 40000MPa / mm to 55000MPa / mm. In some embodiments of the present invention, the CT_LD value of the colored chemically strengthened glass of the present invention is 40000MPa / mm, 41000MPa / mm, 42000MPa / mm, 45000MPa / mm, 48000MPa / mm, 50000MPa / mm, 53000MPa / mm, 55000MPa / mm, 58000MPa / mm or 60000MPa / mm; or within the numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0139] In some embodiments of the present invention, the colored chemically strengthened glass of the present invention is subjected to a sandpaper drop test with 120-grit sandpaper at a thickness of 0.7 mm, and the average sandpaper drop height obtained is greater than 1.60 m, preferably 1.65 to 2.00 m. In some embodiments of the present invention, the colored chemically strengthened glass of the present invention is subjected to a sandpaper drop test with 120-grit sandpaper at a thickness of 0.7 mm, and the average sandpaper drop height obtained can be 1.65 m, 1.68 m, 1.70 m, 1.73 m, 1.75 m, 1.79 m, 1.82 m, 1.87 m, 1.90 m, 1.93 m, 1.96 m, 1.98 m or 2.00 m; or is within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that, in specific embodiments, any of the above ranges can be combined with any other ranges.
[0140] In some embodiments of the present invention, the average value of the proportion of broken pieces of the colored chemically strengthened glass of the present invention is greater than 80%, preferably 85%. In some embodiments of the present invention, the average value of the proportion of broken pieces of the colored chemically strengthened glass of the present invention is 80%, 82%, 85%, 88%, 90%, 93%, 95%, 97% or 99%; or within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges.
[0141] It should be noted that the average value of the percentage of broken fragments after falling refers to the value obtained by dividing the sum of the percentage of broken fragments of at least 5 glass samples after falling by the number of glass samples, which is used to characterize the safety performance of glass falling and breaking, and the formula is as follows:
[0142]
[0143] Where n is the number of glass samples tested, S i The proportion of broken pieces from drops tested for each glass sample;
[0144] The proportion of broken fragments when the glass sample falls refers to the proportion of the weight of the sieve residue to the weight of the glass sample after each glass sample is subjected to a sandpaper drop resistance test with 120 mesh sandpaper at a thickness of 0.7 mm; the weight of the glass sample is the weight of the glass sample weighed before the entire machine falls; the weight of the sieve residue is the weight of the glass sample after it is sieved through a 4-mesh sieve with an aperture of 5.16 mm after it falls and breaks, and the weight of the sieve residue is taken out and weighed.
[0145] In some embodiments of the present invention, the maximum vertical projection size of the average fragments of the colored chemically strengthened glass of the present invention is 4 mm to 35 mm, preferably 5 mm to 35 mm. In some embodiments, the maximum vertical projection size of the average fragments of the colored chemically strengthened glass of the present invention may be 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 10 mm, 12 mm, 15 mm, 20 mm, 24 mm, 28 mm, 30 mm, 33 mm or 35 mm; or within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in specific embodiments, any of the above ranges may be combined with any other ranges.
[0146] It should be noted that the average maximum vertical projection size of the fragments refers to the value obtained by dividing the sum of the average values of the maximum vertical projection sizes of the fragments of at least 5 glass samples by the number of glass samples; the formula is as follows:
[0147]
[0148] Where n is the number of glass samples tested, X i The average value of the maximum vertical projection dimensions of the fragments tested for each glass sample;
[0149] The average value of the maximum vertical projection size of the fragments of the glass sample refers to the average value of the maximum vertical projection size of all glass fragments with a maximum vertical projection size greater than 1 mm selected after each glass sample is subjected to a sandpaper drop resistance test using 120-mesh sandpaper at a thickness of 0.7 mm;
[0150] The specific test method is: each glass sample is subjected to a sandpaper drop resistance test with 120-mesh sandpaper at a thickness of 0.7 mm, and then a photo of the glass sample after it falls and breaks is taken. The photo is imported into the particle size analysis and calculation software: Nanomeasure, and all glass fragments with a maximum vertical projection size greater than 1 mm are selected and marked. The software calculates and outputs the average value of the maximum vertical projection size of all the selected fragments.
[0151] In addition, the present invention provides a method for preparing the colored chemically strengthened glass as described above, comprising the following steps:
[0152] (1) selecting raw material components according to the composition of the substrate glass, mixing them, melting and forming them, and then cooling and annealing them to obtain the substrate glass;
[0153] (2) Chemically strengthening the base glass to obtain colored chemically strengthened glass.
[0154] In the present invention, the preparation of the substrate glass in the preparation method of the colored chemically strengthened glass can be carried out by an existing well-known method. For example, the components are mixed evenly according to the formula, melted and formed, and then cooled and annealed to obtain the substrate glass. Preferably, the mixed raw material components are placed in a platinum crucible and melted in a high-temperature melting furnace or a gas furnace at a melting temperature of 1250°C to 1650°C. More preferably, the melting temperature is 1480°C to 1650°C, and the melting time is 5 to 24 hours. After the melting treatment is completed, the glass liquid is cast into a mold for molding, cooled to 700°C to 1000°C, and then placed in an annealing furnace for annealing. Preferably, the annealing temperature is 250°C to 650°C, and the temperature is kept at 400°C during annealing. 12 to 48 hours; further preferably, first anneal at 550°C to 650°C for 1500-2500 minutes, then cool to 450-500°C within 250-350 minutes, keep warm for 200-400 minutes, then cool to 350-400°C within 250-350 minutes, keep warm for 200-400 minutes, and finally cool to 250-300°C within 250-350 minutes, keep warm for 200-400 minutes, so as to achieve a gradual slow cooling. Then cool to room temperature with the furnace to obtain glass bricks; shape the obtained glass bricks and cut them using a multi-wire cutting machine to obtain glass sheets of the required size, such as 50.0mm×50.0mm×0.7mm in length, width and thickness, 158.8mm×72.8mm×0.7mm, etc.; then perform precision machining (CNC), thinning and polishing to obtain the substrate glass of chemically strengthened glass. In addition, in the present invention, the forming method of the substrate glass includes but is not limited to float, overflow, rolling or casting process.
[0155] In the present invention, the chemical strengthening treatment of the substrate glass in the method for preparing the colored chemically strengthened glass can be performed by a conventionally known method; for example, the chemical strengthening of the substrate glass includes single-step chemical strengthening or multi-step chemical strengthening.
[0156] In some embodiments of the present invention, the single-step chemical strengthening uses a salt bath containing NaNO3, and the content of NaNO3 is preferably 30-100wt%; preferably, the single-step chemical strengthening uses a mixed salt bath containing NaNO3 and KNO3, and the content of KNO3 in the mixed salt bath is preferably 80-100wt%, and the content of NaNO3 is 0-20wt%.
[0157] In some embodiments of the present invention, the temperature of the single-step chemical strengthening is 380-480° C., and preferably, the ion exchange time of the single-step chemical strengthening is 5-10 h.
[0158] In some embodiments of the present invention, the multi-step chemical strengthening includes two steps of chemical strengthening, wherein the first step of chemical strengthening uses a salt bath containing NaNO3, preferably the content of NaNO3 is 30-100wt%; the second step of chemical strengthening uses a salt bath containing KNO3, preferably the content of KNO3 is 60-100wt%.
[0159] In some embodiments of the present invention, the first step of chemical strengthening uses a mixed salt bath containing NaNO3 and KNO3, wherein the content of NaNO3 is 30-100wt%, and the content of KNO3 is 0-70wt%; the second step of chemical strengthening uses a mixed salt bath containing NaNO3 and KNO3, wherein the content of KNO3 is 80-100wt%, and the content of NaNO3 is 0-20wt%.
[0160] In some embodiments of the present invention, the temperature of the first step of chemical strengthening is 380-480°C, and the preferred ion exchange time is 3-10h; preferably, the temperature of the second step of chemical strengthening is 380-480°C, and the preferred ion exchange time is 1-5h.
[0161] In some embodiments of the present invention, the thickness t of the colored chemically strengthened glass obtained by the method for preparing the colored chemically strengthened glass is not particularly limited, for example, it can be 0.4 to 2.0 mm; preferably 0.4 to 1.0 mm. In some embodiments of the present invention, the thickness t of the colored chemically strengthened glass of the present invention can be 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 2.0 mm, or a range formed by any two of the above values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0162] In some embodiments of the present invention, the DOL_0 of the colored chemically strengthened glass obtained by the preparation method of the colored chemically strengthened glass is 0.14t≤DOL_0≤0.25t, where t is the thickness of the colored chemically strengthened glass; the thickness of the colored chemically strengthened glass before and after chemical strengthening is very small and almost negligible, that is, the thickness of the substrate glass is very small compared with the thickness of the chemically strengthened glass obtained by chemically strengthening the substrate glass. In some embodiments of the present invention, the DOL_0 of the colored chemically strengthened glass obtained by the method for preparing the colored chemically strengthened glass is preferably 0.14t≤DOL_0≤0.24t; it can also be: 0.14t, 0.15t, 0.154t, 0.16t, 0.165t, 0.17t, 0.175t, 0.18t, 0.19t, 0.20t, 0.21t, 0.22t, 0.23t, 0.24t, 0.25t or a range formed by any two of the above values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0163] In some embodiments of the present invention, the CS_50 of the colored chemically strengthened glass of the present invention is 40MPa to 120MPa, preferably, CS_50 is 80MPa to 110MPa. In some embodiments of the present invention, the CS_50 of the colored chemically strengthened glass of the present invention is 40MPa, 45MPa, 50MPa, 55MPa, 60MPa, 65MPa, 70MPa, 75MPa, 80MPa, 82MPa, 84MPa, 86MPa, 88MPa, 90MPa, 92MPa, 94MPa, 96MPa, 98MPa, 100MPa, 102MPa, 106MPa, 108MPa, 110MPa, 112MPa, 115MPa or 120MPa; or within the numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0164] In some embodiments of the present invention, the |CT_AV| of the colored chemically strengthened glass obtained by the method for preparing the colored chemically strengthened glass of the present invention is 60MPa to 100MPa. In some embodiments of the present invention, the |CT_AV| of the colored chemically strengthened glass of the present invention may be 60.00MPa, 61.00MPa, 62.81MPa, 63.00MPa, 64.00MPa, 65.25MPa, 66.17MPa, 67.04MPa, 67.74MPa, 70.00MPa, 80.00MPa, 85.00MPa, 90.00MPa, 95.00MPa or 100.00MPa; or within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges may be combined with any other ranges.
[0165] In some embodiments of the present invention, the CT_LD value of the colored chemically strengthened glass obtained by the preparation method of the colored chemically strengthened glass is 40000MPa / mm~60000MPa / mm, preferably, the CT_LD value is 40000MPa / mm~55000MPa / mm. In some embodiments of the present invention, the CT_LD value of the colored chemically strengthened glass obtained by the preparation method of the colored chemically strengthened glass is 40000MPa / mm, 41000MPa / mm, 42000MPa / mm, 45000MPa / mm, 48000MPa / mm, 50000MPa / mm, 53000MPa / mm, 55000MPa / mm, 58000MPa / mm or 60000MPa / mm; or within the numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0166] In some embodiments of the present invention, the colored chemically strengthened glass obtained by the method for preparing colored chemically strengthened glass has an average sandpaper drop resistance height greater than 1.60m, preferably 1.65-2.00m, when the thickness is 0.7mm, and the average sandpaper drop resistance height obtained by the sandpaper drop resistance test using 120-grit sandpaper is greater than 1.60m, preferably 1.65-2.00m. In some embodiments of the present invention, the colored chemically strengthened glass obtained by the method for preparing colored chemically strengthened glass has an average sandpaper drop resistance height obtained by the sandpaper drop resistance test using 120-grit sandpaper when the thickness is 0.7mm, which may be 1.65m, 1.68m, 1.70m, 1.73m, 1.75m, 1.79m, 1.82m, 1.87m, 1.90m, 1.93m, 1.96m, 1.98m or 2.00m; or is within the numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges may be combined with any other ranges.
[0167] In some embodiments of the present invention, the average value of the proportion of broken fragments of the colored chemically strengthened glass obtained by the method for preparing the colored chemically strengthened glass is greater than 80%, preferably 85%. In some embodiments of the present invention, the average value of the proportion of broken fragments of the colored chemically strengthened glass obtained by the method for preparing the colored chemically strengthened glass is 80%, 82%, 85%, 88%, 90%, 93%, 95%, 97% or 99%; or within the numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges.
[0168] In some embodiments of the present invention, the maximum vertical projection size of the average fragments of the colored chemically strengthened glass obtained by the method for preparing the colored chemically strengthened glass is 4 mm to 35 mm, preferably 5 mm to 35 mm. In some embodiments of the present invention, the maximum vertical projection size of the average fragments of the colored chemically strengthened glass of the present invention may be 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 10 mm, 12 mm, 15 mm, 20 mm, 24 mm, 28 mm, 30 mm, 33 mm or 35 mm; or within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges.
[0169] The present invention provides a use of the colored chemically strengthened glass as described above or the colored chemically strengthened glass prepared by the method for preparing the colored chemically strengthened glass as described above in a mobile phone display screen, a tablet computer display screen, a handheld game console, an electronic terminal, a portable digital device, a vehicle central control screen, an electronic whiteboard glass, a smart home touch screen, a vehicle windshield, an aircraft windshield or an aircraft windshield.
[0170] The various glasses of the present invention are tested by the following methods:
[0171] Young's modulus test: The UMS-100 ultrasonic material characterization system was used to test the Young's modulus of glass using ultrasonic echo analysis.
[0172] Surface stress test: Surfaces CS_50, DOL_0 and |CT_AV| were tested using a stress meter SLP-2000 from Luceo (Japan).
[0173] The test conditions are: light source wavelength 518nm, SOC = 28.6 (nm / cm) / MPa, refractive index = 1.51, exposure time: 5000usec. When testing CS_50, DOL_0, |CT_AV|, you need to first drop a conductive liquid on the stress meter, then wipe the glass sample to be tested clean, and place it on the test path to test its stress value. SLP-2000 uses a conductive liquid with a refractive index of 1.51. FSM-6000 uses a conductive liquid with a refractive index of 1.72.
[0174] CT_LD is calculated as follows:
[0175]
[0176] Where: t represents the thickness of the glass sheet, in mm; DOL_0 represents the depth of the compressive stress layer, in μm; CT_AV represents the internal average tensile stress, and its absolute value is taken in the calculation, in MPa. It should be understood that in the calculation formula of the tensile stress linear density, (1000t / 2-DOL_0) is to substitute the data for the calculation and obtain the calculation result, and the unit does not participate in the calculation.
[0177] CT_LD max Test: In the present invention, a 100wt% sodium nitrate salt bath at 450°C is used as the test CT_LD max The salt bath condition is adopted, and the SLP-2000 stress meter is used as the test instrument for testing the tensile stress linear density CT_LD. The specific method is: the substrate glass sample to be tested is placed in a 100wt% sodium nitrate salt bath at 450°C for chemical strengthening. During the strengthening period, the glass sample is taken out every 0.5h to test the CT_LD value inside it. After each glass sample is taken out for testing, the glass sample is immediately placed in the salt bath and continued to be strengthened. When the next test time point is reached, the glass sample is taken out for testing again, and the above test process is repeated to record the tested CT_LD value. When it is found that the measured CT_LD value begins to decrease after increasing to a certain value m, it is determined that the value m is the maximum tensile stress linear density CT_LD that can be obtained by strengthening the substrate glass sample in the salt bath condition, that is, in a 100wt% sodium nitrate salt bath at 450°C.max .
[0178] Bifurcation threshold test: First test the substrate glass with a thickness of 0.7 mm corresponding to a certain glass formula, perform ion exchange in a certain salt bath, and obtain the maximum value of the tensile stress linear density CT_LD max Then, chemically strengthened glass samples with different CT_LD were strengthened under the salt bath conditions, for example, CT_LD ranged from 30000 MPa / mm to CT_LD max , with an increase of about 1000MPa / mm, 1500MPa / mm or 2000MPa / mm, and CT_LD is obtained by testing with an SLP-2000 stress meter. For example, in the present invention, a substrate glass with a thickness of 0.7mm corresponding to the glass formula to be tested is strengthened in a 100wt% sodium nitrate salt bath at 450°C to obtain chemically strengthened glass samples with CT_LD of about 30000MPa / mm, about 31000MPa / mm, about 32000MPa / mm, about 33000MPa / mm, about 34000MPa / mm, and about 36000MPa / mm, respectively, and then these chemically strengthened glass samples are subjected to immediate fracture tests in order of CT_LD values from low to high. The center point of the chemically strengthened glass sample is used as the failure point, and a "stress release device" is used to cause cracks to form at the failure point. A chemically strengthened glass sample with crack bifurcation is selected, and the minimum CT_LD value of the chemically strengthened glass sample with crack bifurcation is used as the bifurcation threshold of the chemically strengthened glass prepared from the base glass of the formula.
[0179] Immediate fracture test: The center point of the chemically strengthened glass sample is used as the breaking point, and a "stress release device" is used to generate cracks at the breaking point, so that the cracks extend under the action of the internal tensile stress, rather than generating starbursts due to excessive impact force. When the crack of the chemically strengthened glass bifurcates, the minimum tensile stress linear density value of the chemically strengthened glass sample is the bifurcation threshold. A certain number of substrate glass products are strengthened under the same salt bath conditions and different ion exchange times to obtain glass samples with different tensile stress linear densities. According to the tensile stress linear density values from low to high, fracture tests are performed on the multiple glass samples obtained by strengthening. After the immediate fracture test, check whether the crack of the glass sample bifurcates, find the glass samples with crack bifurcations, and determine the minimum tensile stress linear density (CT_LD) value corresponding to these glass samples, which is the bifurcation threshold of the chemically strengthened glass corresponding to the substrate glass.
[0180] The stress relief device Figure 1, where 1 represents the height adjustment rail, 2 represents the start adjustment rail, 3 represents the indenter, and 4 represents the chemically strengthened glass sample; the device uses pneumatic impact, and the probe uses a Vickers diamond indenter and is fixed with a rail to ensure that the indenter impacts the glass surface vertically. It is also equipped with a pressure sensor, which controls the impact force in combination with air pressure regulation, so that the damage point only induces delayed fracture or only extends two cracks instead of generating starbursts, thereby minimizing the influence of external forces on the damage state. In the immediate fracture experiment, the crack needs to be extended as Figure 2 As shown in a or b in Figure 2 As shown in c.
[0181] CIELAB color chromaticity index test: Put the sheet glass into the spectrophotometer, and measure the transmittance of the 0.7mm thick glass in the wavelength range of 360nm to 740nm and the L*, a*, b* chromaticity values under the CIE light source D65 condition in the transmission mode. The spectrophotometer used is the Konica Minolta CM-3600A; the results are shown in Table 1-2.
[0182] Average sandpaper drop height test
[0183] Average sandpaper drop resistance height: The value obtained by dividing the sum of the sandpaper drop resistance heights measured for multiple glass samples by the number of samples measured. It is used to characterize the glass's resistance to cracking on the contact surface.
[0184] Take at least 10 glass samples from each batch for testing, and take the average value of the sandpaper drop resistance height of all glass samples. The formula is as follows:
[0185]
[0186] Wherein, n is the number of glass samples tested in each batch, and hi is the sandpaper drop resistance height of a single glass sample tested.
[0187] Among them, the test method for the glass sample's resistance to sandpaper drop height is:
[0188] Step 1: Stick the glass sample to be tested with a length, width and thickness of 158.8mm×72.8mm×0.7mm on the front of the 200g model machine;
[0189] Step 2: Place the model machine on the Green Figure LT-SKDL-CD drop machine, with the glass sample facing the sandpaper, and drop it from a certain drop height, impacting the 120-grit sandpaper located directly below the model machine, simulating the normal drop posture of a mobile phone.
[0190] If the glass sample does not break, the drop height of the model machine is increased in a certain pattern. For example, the drop height starts from 0.4m, and the sample is dropped once. If it does not break, the drop height is increased by 0.1m each time until the glass sample breaks.
[0191] Step 3: The last drop height of the glass sample when it breaks is recorded as the anti-sandpaper drop height. For example, if the drop height when it breaks is 0.5m, the anti-sandpaper drop height of the sample is 0.4m.
[0192] Drop and break test:
[0193] Average value of the proportion of broken fragments when dropped: the value obtained by dividing the sum of the proportion of broken fragments measured for at least 5 glass samples by the number of samples measured, which is used to characterize the safety performance of glass when dropped and broken; the formula is as follows:
[0194] Where n is the number of glass samples tested, S i The percentage of broken pieces from a single glass sample tested.
[0195] The proportion of broken fragments when the glass sample falls refers to the proportion of the weight of the sieve residue to the weight of the glass sample after each glass sample is subjected to a sandpaper drop resistance test with 120 mesh sandpaper at a thickness of 0.7 mm; the weight of the glass sample is the weight of the glass sample weighed before the entire machine falls; the weight of the sieve residue is the weight of the glass sample after it is sieved through a 4-mesh sieve with an aperture of 5.16 mm after it falls and breaks, and the weight of the sieve residue is taken out and weighed.
[0196] Average maximum vertical projection size of fragments: The value obtained by dividing the sum of the average maximum vertical projection sizes of the fragments measured from at least 5 glass samples by the number of samples measured is used to characterize the safety performance of glass falling and breaking; the formula is as follows:
[0197]
[0198] Where n is the number of glass samples tested, X i The average value of the maximum vertical projection dimension of the fragments tested for a single glass sample.
[0199] The average value of the maximum vertical projection size of the fragments of the glass sample refers to the average value of the maximum vertical projection size of all glass fragments with a maximum vertical projection size greater than 1 mm selected after each glass sample is subjected to a sandpaper drop resistance test using 120-mesh sandpaper at a thickness of 0.7 mm;
[0200] The specific test method is: each glass sample is subjected to a sandpaper drop resistance test with 120-mesh sandpaper at a thickness of 0.7 mm, and then a photo of the glass sample after it falls and breaks is taken. The photo is imported into the particle size analysis and calculation software: Nanomeasure, and all glass fragments with a maximum vertical projection size greater than 1 mm are selected and marked. The software calculates and outputs the average value of the maximum vertical projection size of all the selected fragments.
[0201] The present invention is described below by specific embodiments:
[0202] 1: Specific operation examples
[0203] According to the material recipe of Example 1 in Table 1, each raw material is accurately weighed in proportion, the total mass of the raw materials is 1600 g, 4 wt‰ of a clarifier sodium chloride (6.4 g sodium chloride) is added, and the mixture is fully mixed to obtain a mixture. The mixture is placed in a platinum crucible, heated to 1650°C in a high-temperature melting furnace and melted for 10 hours. After the melting process is completed, the glass liquid is cast into a mold and cooled to form. After cooling to 800°C, it is placed in an annealing furnace and annealed at 560°C for 2000 minutes; then the temperature is reduced to 500°C within 300 minutes, and the temperature is kept for 300 minutes. Then the temperature is reduced to 400°C within 300 minutes and the temperature is kept for 300 minutes. Then the temperature is reduced to 300°C within 300 minutes and the temperature is kept for 300 minutes, so as to achieve a gradual slow cooling; then the temperature is cooled to room temperature with the furnace to obtain glass bricks; the obtained glass bricks are shaped and cut using a multi-wire cutting machine to obtain glass sheets of the required size, such as 50.0mm×50.0mm×0.7mm in length, width and thickness, 158.8mm×72.8mm×0.7mm, etc.; then precision machining (CNC), thinning and polishing are performed to obtain the substrate glass of chemically strengthened glass.
[0204] Next, the substrate glass sample with a thickness of 0.7 mm obtained above was treated according to a two-step chemical strengthening process to obtain a colored chemically strengthened glass. The specific two-step chemical strengthening process conditions are described in Table 3.
[0205] Examples 2-14 and Comparative Examples 1-4 were prepared under the same operating conditions as Example 1, except for the glass compositions of the substrate glasses shown in Tables 1 and 2 and the strengthening process conditions in Tables 3-4.
[0206] In the present invention, for various samples of substrate glass that has not been chemically strengthened, chemically strengthened colored chemically strengthened glass, the comparison of a* and b* parameters shows that for D65 light source, the a* and b* parameters change very little; the maximum change is about 0.06; the measurement shows that the color change caused by conventional ion exchange is very small.
[0207] Table 1: Substrate glass of Examples 1-5 and Comparative Examples 1-4
[0208]
[0209]
[0210] Table 2 Base glass of Examples 6-14
[0211]
[0212]
[0213]
[0214] Table 3 Process conditions and properties of chemically strengthened glass
[0215]
[0216]
[0217] Table 4 Process conditions and properties of chemically strengthened glass
[0218]
[0219]
[0220] By comparing Example 1 with Comparative Example 1, it can be seen that under the same chemical strengthening conditions, the DOL_0 and CS_50 of the colored chemically strengthened glass prepared by adding 0.10 mol% erbium oxide in Example 1 are higher than those in Comparative Example 1, and the drop resistance is also improved.
[0221] By comparing Example 5 with Comparative Example 2, it can be seen that the amount of erbium oxide added in Comparative Example 2 is 2.20 mol%, and when it exceeds the amount of 2.00 mol% added in Example 5, the bifurcation threshold of Example 5 decreases significantly; in addition, under the same chemical strengthening conditions, the fragments of the colored chemically strengthened glass prepared in Example 5 are relatively large after being broken, and the average proportion of broken fragments is 81.59%, which has high safety; while the fragments of the colored chemically strengthened glass prepared in Comparative Example 2 are too small after being broken, which is easy to cause splashing, and the average proportion of broken fragments is 0, which has a safety hazard.
[0222] It can be seen from Table 1 and Table 3 that the CT_LD value of the colored chemically strengthened glass prepared in Examples 1 to 5 of the present invention is 41373-41654 MPa / mm, the |CT_AV| value is 62.81-67.74 MPa, the DOL_0 is 118-135 μm, the sandpaper drop resistance height is 1.68-1.79 m, the average drop-broken fragment ratio is 81.59-93.36%, and the average maximum vertical projection size of the fragments is 5.98-9.17 mm; the colored chemically strengthened glass has high strength, excellent drop resistance and high safety performance.
[0223] As shown in Table 2 and Table 4, the CT_LD value of the colored chemically strengthened glass prepared in Examples 6 to 14 of the present invention is 41084-41591 MPa / mm, the |CT_AV| value is 62.02-67.54 MPa, the DOL_0 is 118-136 μm, the sandpaper drop height is 1.66-1.78 m, the average drop broken fragment ratio is 80.98-85.21%, and the average maximum vertical projection size of the fragments is 5.93-8 .11mm; the CIELAB color chromaticity index of the substrate glass at a thickness of 0.7mm under the CIE light source D65 condition is: L* value is 86.59-92.24, a* value is 1.91-7.44, and b* value is -10.50-5.09; it can be seen that the colored chemically strengthened glass prepared in Examples 6-14 of the present invention has high strength, excellent anti-drop performance and high safety performance as well as desirable pleasing colors.
[0224] In summary, the present invention obtains a colored chemically strengthened glass that has high strength, high drop resistance and safety by adjusting the dosage of erbium oxide and the formula design of the substrate glass; further, adding an appropriate amount of additives and erbium oxide to form a color combination can prepare a colored chemically strengthened glass that has high strength, high drop resistance, high safety and a pleasing aesthetic effect.
[0225] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.
Claims
1. A colored chemically strengthened glass, characterized in that: The colored chemically strengthened glass is obtained by chemically strengthening a base glass. The base glass includes the following components in molar percentage: SiO2 58.00~75.00mol%; Al2O38.00~16.00mol%; B2O3 0.00~5.00mol%; Y2O31.00~8.00mol%; La2O3 0.10-5.00mol%; MgO 1.00~8.00mol%; Na2O 3.00~8.00mol%; Li2O 7.00~15.00mol%; Er2O3 0.10~2.00mol%; In terms of molar percentage, the components of Er2O3, Y2O3, MgO and Al2O3 in the substrate glass satisfy the following relationship: 0.004≤Er2O3 / (2.450×Y2O3+1.620×MgO+1.078×Al2O3)≤0.076; The thickness of the colored chemically strengthened glass is t 0.4 to 2.0 mm; The CS_50 of the colored chemically strengthened glass is 60 MPa to 120 MPa.
2. The colored chemically strengthened glass according to claim 1, characterized in that: The CIELAB color chromaticity index of the substrate glass under the CIE light source D65 condition at a thickness of 0.7 mm is: L* value is 91.00-97.00, a* value is 1.00-10.00, and b* value is -4.00--0.
10.
3. The colored chemically strengthened glass according to claim 1, wherein: The bifurcation threshold of the substrate glass is 39000MPa / mm to 60000MPa / mm.
4. The colored chemically strengthened glass according to claim 3, characterized in that: The bifurcation threshold of the substrate glass is 39000MPa / mm to 50000MPa / mm.
5. The colored chemically strengthened glass according to claim 2, wherein: The bifurcation threshold of the substrate glass is 39000MPa / mm to 60000MPa / mm.
6. The colored chemically strengthened glass according to claim 1, wherein: The CS_50 of the colored chemically strengthened glass is 80 MPa to 110 MPa; and / or, The DOL_0 of the colored chemically strengthened glass is 0.14t≤DOL_0≤0.25t, where t is the thickness of the colored chemically strengthened glass; and / or, The CT_LD of the colored chemically strengthened glass is 40000 MPa / mm to 60000 MPa / mm.
7. The colored chemically strengthened glass according to claim 6, wherein: The CS_50 is 80MPa to 108MPa; and / or the CT_LD value is 40000MPa / mm to 55000MPa / mm.
8. The colored chemically strengthened glass according to claim 3, wherein: The CS_50 of the colored chemically strengthened glass is 80 MPa to 110 MPa; and / or, The DOL_0 of the colored chemically strengthened glass is 0.14t≤DOL_0≤0.25t, where t is the thickness of the colored chemically strengthened glass; and / or, The CT_LD of the colored chemically strengthened glass is 40000 MPa / mm to 60000 MPa / mm.
9. The colored chemically strengthened glass according to claim 1, wherein: The colored chemically strengthened glass has an average sandpaper drop resistance height greater than 1.60 m obtained by performing a sandpaper drop resistance test on the colored chemically strengthened glass with a thickness of 0.7 mm using 120-mesh sandpaper.
10. The colored chemically strengthened glass according to claim 9, characterized in that: The colored chemically strengthened glass has an average sandpaper drop resistance height of 1.65 to 2.00 m obtained by performing a sandpaper drop resistance test on the colored chemically strengthened glass with a thickness of 0.7 mm using 120-mesh sandpaper.
11. The colored chemically strengthened glass according to claim 3, wherein: The colored chemically strengthened glass has an average sandpaper drop resistance height greater than 1.60 m obtained by performing a sandpaper drop resistance test on the colored chemically strengthened glass with a thickness of 0.7 mm using 120-mesh sandpaper.
12. The colored chemically strengthened glass according to claim 6, wherein: The colored chemically strengthened glass has an average sandpaper drop resistance height greater than 1.60 m obtained by performing a sandpaper drop resistance test on the colored chemically strengthened glass with a thickness of 0.7 mm using 120-mesh sandpaper.
13. The colored chemically strengthened glass according to claim 1, wherein: t is 0.4~1.0mm.
14. The colored chemically strengthened glass according to claim 13, wherein: t is 0.4-0.8mm.
15. The colored chemically strengthened glass according to claim 13, wherein: t is 0.7mm.
16. The colored chemically strengthened glass according to any one of claims 1 to 15, characterized in that: The average value of the percentage of broken pieces of the colored chemically strengthened glass when dropped is greater than 80%; The average value of the percentage of broken pieces after falling refers to the value obtained by dividing the sum of the percentage of broken pieces after falling of at least 5 glass samples by the number of glass samples; The proportion of broken fragments when the glass sample falls refers to the proportion of the weight of the sieve residue to the weight of the glass sample after each glass sample is subjected to a sandpaper drop resistance test with 120 mesh sandpaper at a thickness of 0.7 mm; the weight of the glass sample is the weight of the glass sample weighed before the entire machine falls; the weight of the sieve residue is the weight of the glass sample after it is sieved through a 4-mesh sieve with an aperture of 5.16 mm after it falls and breaks, and the weight of the sieve residue is taken out and weighed.
17. The colored chemically strengthened glass according to any one of claims 1 to 13, characterized in that: The maximum vertical projection size of the average fragments of the colored chemically strengthened glass is 4 mm to 35 mm; The average maximum vertical projection size of the fragments refers to the value obtained by dividing the sum of the average values of the maximum vertical projection sizes of the fragments of at least 5 glass samples by the number of glass samples; The average value of the maximum vertical projection size of the fragments of the glass sample refers to the average value of the maximum vertical projection size of all glass fragments with a maximum vertical projection size greater than 1 mm after each glass sample is subjected to a sandpaper drop resistance test with 120-mesh sandpaper at a thickness of 0.7 mm.
18. A method for preparing colored chemically strengthened glass according to any one of claims 1 to 17, characterized in that: The steps include: (1) selecting raw materials according to the glass composition, mixing them, melting and forming them, cooling and annealing them to obtain a substrate glass; (2) The base glass is chemically strengthened to obtain the colored chemically strengthened glass.
19. Use of the colored chemically strengthened glass according to any one of claims 1 to 17 or the colored chemically strengthened glass prepared by the preparation method according to claim 18 in mobile phone display screens, tablet computer display screens, handheld game consoles, electronic terminals, portable digital devices, vehicle central control screens, electronic whiteboard glass, smart home touch screens, vehicle windshields, aircraft windshields or aircraft windshields.
Citation Information
Patent Citations
Glass composition
CN108298811A
Microcrystalline glass and substrate thereof
CN109867447A
Chemically strengthened glass, and glass for chemical strengthening
CN110255892A
Microcrystalline glass, microcrystalline glass product and manufacturing method thereof
CN111099825A
Master glass, chemically strengthened glass, 3D hot bending glass and hot bending strengthened glass
CN116081945A